The Charisma of Women's Transformational Leadership In Improving Institutional Brand Image of Learning Technology - Yuhana, Nihayatul Laili; Maunah, Binti; Safi’I, Asrop (Yayasan Indonesia Emerging Literacy Education, 2025)
One of the elements that make education more qualified is education, Various problems that are inseparable from life as an organization. These problems cover several aspects, such as defining goals, determining policies, developing programs, employing people, providing facilities, achieving results and coordinating separate activities. All of these activities require the involvement of people with different ability backgrounds, such as professional supervisors, and other personnel. This study aims to describe: charisma of women's transformational leadership in improving institutional brand image. This study uses a qualitative approach. This type of research can be used to find and understand what is hidden behind a phenomenon that is sometimes difficult to know or understand. Data collection in this study uses in-depth interview techniques, observation, and documentation where the data sources are from people , documents ( paper ) and places ( place ). The Charisma of Transformational Women's Leadership in Improving the Institutional Brand Image at the Bahrul Ulum Mambaiyyah Islamic Boarding School (BUM) South Lampung Regency is manifested in attitude to know; High commitment to the programs and SOPs that have been jointly determined in the meeting forum, Willingness to share authority and responsibility for evaluation and training. Effective communication, Moral ethics, Diligence in evaluation and training. He always uses songs/poems that are really liked by his congregation, which give coolness to the heart. There are lots of Mbah Nyai's poems like in his book of heart-soothing poetry